2017
DOI: 10.21500/20112084.2794
|View full text |Cite
|
Sign up to set email alerts
|

Intención de emprendimiento en estudiantes de cinco países latinoamericanos y su relación con liderazgo, propensión al riesgo y locus de control,

Abstract: The aim of this study was to determine if entrepreneurial intention, based on Ajzen's model of planned behavior (1991), can be predicted by risk propensity, internal locus of control and leadership skills. Six standardized and reliable instruments were applied to 1493 undergraduate university business students in Latin American countries, selected through non-random quota sampling in accordance with their formation level in each of the five participating universities. Using structural equation techniques, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…Despite the empirical validation of these proposals that have deepened our understanding of entrepreneurial initiatives, there is still only limited evidence on the aspects that precede and stimulate entrepreneurial intentions [39][40][41][42]. As Lanero et al [36] and Liñan and Chen [26] point out, the reasons for the lack of research on entrepreneurial intentions may be due to the researchers' different conceptual approaches toward entrepreneurial intention, in particular with regard to the variables that regulate and act as antecedents to such an intention [43][44][45].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite the empirical validation of these proposals that have deepened our understanding of entrepreneurial initiatives, there is still only limited evidence on the aspects that precede and stimulate entrepreneurial intentions [39][40][41][42]. As Lanero et al [36] and Liñan and Chen [26] point out, the reasons for the lack of research on entrepreneurial intentions may be due to the researchers' different conceptual approaches toward entrepreneurial intention, in particular with regard to the variables that regulate and act as antecedents to such an intention [43][44][45].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Obschonka et al (2010) encontraron que, incentivando el emprendimiento durante la adolescencia, se logra que durante la adultez esta actividad se vea como algo natural y seguro de que pueda suceder. En el estudio realizado por Contreras et al (2017) con muestras de los países de Latinoamérica, ellos encontraron que los estudiantes que están próximos a egresar de la universidad muestran una mayor intención emprendedora que los que están iniciando sus estudios universitarios. Por otro lado, según el GEM, en países como Chile, Colombia, Ecuador, Perú y Venezuela los universitarios jóvenes tienen una alta IE.…”
Section: Nivel De Estudiosunclassified
“…Para que surja una persona que quiera emprender es necesario que exista una oportunidad emprendedora y la intención y capacidad para aprovecharla, haciendo frente a la incertidumbre, al riesgo (Fayolle y Liñán, 2014, Kautonen et al, 2015 y al miedo al fracaso. Esto implica que la IE del individuo debe considerar variables individuales y ambientales (Contreras et al, 2017). Krueger et al (2000) establecieron que, para estimular el desarrollo económico mediante la creación de nuevas empresas es necesario incrementar la percepción de viabilidad y deseabilidad en los individuos, lo cual propicia el incremento de la IE.…”
Section: Introductionunclassified
“…First, certain elements are considered: a) entrepreneurship is a topic least explored in Latin America (Villegas, Amorós, 2019); b) although, the interest in studying entrepreneurship in Latin America has increased in recent years (Ketelhöhn, Ogliastri, 2013), understanding entrepreneurial behavior in this region can be complex because some studies have found difficulties in explaining this phenomenon with foreign theoretical models (e.g., Guzmán-Alfonso, Guzmán-Cuevas, 2012). Therefore, this could require a particular vision of the Latin American context; and, c) There are few studies that have described these variables among University students (e.g., Contreras et al, 2017). Regarding the context: a) this region, according to the Global Entrepreneurship Monitor (GEM, 2018), presents the high levels of entrepreneurial activity; b) Latin American entrepreneurs have experienced problems being competitive (Vidal, 2008;Lederman et al, 2014); e) and, finally, these countries have tried to strengthen business education programs (Sánchez et al, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In this context, entrepreneurial education could be an alternative to reduce youth unemployment problems (Sánchez et al, 2017). In addition, there are few studies on entrepreneurship among Latin American students (e.g., Contreras et al, 2017). In the case of Mexico, education has played an important role in the development of entrepreneurial oriented human capital (González, Husted, 2011).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%